Phosphoproteomic profiling reveals a defined genetic program for osteoblastic lineage commitment of human bone marrow–derived stromal stem cells - Barrio-Hernandez, Inigo; Jafari, Abbas; Rigbolt, Kristoffer T.G.; Hallenborg, Philip; Sanchez-Quiles, Virginia; Skovrind, Ida; Akimov, Vyacheslav; Kratchmarova, Irina; Dengjel, Joern; Kassem, Moustapha; Blagoev, Blagoy

(untitled) (Genome Research, 2020)
Bone marrow–derived mesenchymal stem cells (MSCs) differentiate into osteoblasts upon stimulation by signals present in their niche. Because the global signaling cascades involved in the early phases of MSCs osteoblast (OB) differentiation are not well-defined, we used quantitative mass spectrometry to delineate changes in human MSCs proteome and phosphoproteome during the first 24 h of their OB lineage commitment. The temporal profiles of 6252 proteins and 15,059 phosphorylation sites suggested at least two distinct signaling waves: one peaking within 30 to 60 min after stimulation and a second upsurge after 24 h. In addition to providing a comprehensive view of the proteome and phosphoproteome dynamics during early MSCs differentiation, our analyses identified a key role of serine/threonine protein kinase D1 (PRKD1) in OB commitment. At the onset of OB differentiation, PRKD1 initiates activation of the pro-osteogenic transcription factor RUNX2 by triggering phosphorylation and nuclear exclusion of the histone deacetylase HDAC7.